Assessing differences between short-term, high-rate offenders and long-term, low-rate offenders - Piquero, Alex R. (Criminal justice and behavior, 2010)
In empirically assessing offending trajectory groups, some researchers have identified unexpected classes of offenders. Two such groups are (a) short-term, high-rate offenders and (b) long-term, low-rate offenders. On some aggregate benchmarks, such as lifetime volume of crime, these two groups of offenders may be comparable. Yet a more detailed examination of their careers may reveal important distinctions regarding the correlates of offending, the extent of involvement in crime, and associated costs to society. Furthermore, unpacking the history, profile, and trajectory of these two groups of offenders may suggest unique policy options. The authors examined the question of equivalency in these groups and the factors that contribute to their offending using longitudinal data from the Cambridge Study in Delinquent Development through age 40. Theoretical and policy implications associated with criminal justice response are discussed.